2007
DOI: 10.1159/000111118
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor, Hypoxia-Inducible Factor 1 Alpha and CD34 Expressions in Early-Stage Gastric Tumors: Relationship with Pathological Factors and Prognostic Impact on Survival

Abstract: Background: Angiogenesis is one of the key steps in solid tumor growth and metastasis. We planned to investigate the prognostic significance of vascular endothelial growth factor (VEGF), hypoxia-inducible factor 1α (HIF-1α) and CD34 expressions as markers of angiogenesis in gastric cancer. Patients and Methods: We retrospectively reviewed the medical records of 51 gastric cancer patients who had total or subtotal gastrectomy at Marmara University Hospital from 1990 to 2004 and evaluated the expression of VEGF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 73 publications
3
20
0
Order By: Relevance
“…We provide experimental evidence for reduced metastatic properties of gastric cancer cells through functional inactivation of HIF-1a, even under conditions of ambient oxygen. Our characterisation of the temporospatial expression patterns of HIF-1a protein during the pathogenesis of human gastric adenocarcinoma are in line with earlier studies showing HIF-1a protein expression in the majority of human gastric cancer samples (Urano et al, 2006;Cabuk et al, 2007;Griffiths et al, 2007). In contrast, two Japanese studies reported lower percentages of HIF-1a-positive tumour cells in human gastric adenocarcinoma samples Sumiyoshi et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We provide experimental evidence for reduced metastatic properties of gastric cancer cells through functional inactivation of HIF-1a, even under conditions of ambient oxygen. Our characterisation of the temporospatial expression patterns of HIF-1a protein during the pathogenesis of human gastric adenocarcinoma are in line with earlier studies showing HIF-1a protein expression in the majority of human gastric cancer samples (Urano et al, 2006;Cabuk et al, 2007;Griffiths et al, 2007). In contrast, two Japanese studies reported lower percentages of HIF-1a-positive tumour cells in human gastric adenocarcinoma samples Sumiyoshi et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis of EGC samples detected specific nuclear expression of HIF-1a in only 15% of the examined cases. Although this result is in line with one previous study showing specific HIF-1a staining in 29% of T1 tumours (Sumiyoshi et al, 2006), two other articles reported strikingly different results (HIF-1a positivity in 68 and 100% of T1 tumours) (Urano et al, 2006;Cabuk et al, 2007). Given these sharp contrasts, a definite agreement on the expression pattern of HIF-1a in T1 gastric adenocarcinomas cannot be reached at this point and should be clarified by future work.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…An increased expression of vascular endothelial growth factor (VEGF) and vascular endothelial growth factor receptors (VEGFR1-4) is known to promote angiogenesis, and is therefore associated with more aggressive forms of gastric cancer (41)(42)(43). Despite promising in vitro results, clinical trials with the VEGF-A monoclonal antibody bevacizumab failed to show a significant improvement in patient survival rates when supplemented with first-line chemotherapy (44,45).…”
Section: Genetic Aberrations and Mutations Associated With Gastricmentioning
confidence: 99%
“…Midkine (MK) is a recently discovered heparin-binding growth factor with strong differentiation, mitotic and angiogenesis activity (7)(8)(9). Vascular endothelial growth factor (VEGF) promotes vascular endothelial cell proliferation and its high expression in tumors is significantly associated with advanced disease and poor prognosis (10)(11)(12). We investigated MK and VEGF expression levels in gastric cancer specimens by immunohistochemistry, and examined their relationship to prognostic factors of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%